2021
DOI: 10.1088/1741-4326/ac146f
|View full text |Cite
|
Sign up to set email alerts
|

Impact of magnetic islands on plasma flow and turbulence in W7-X

Abstract: The effect of magnetic islands on plasma flow and turbulence has been experimentally investigated in the stellarator W7-X. Magnetic configurations with the 5/5 magnetic island positioned at the plasma edge, inside the last closed flux surface, are studied. The main diagnostic used in the present work is a V-band Doppler reflectometer that allows the measurement of the perpendicular plasma flow and density fluctuations with good spatial resolution. A characteristic signature of the 5/5 magnetic island is clearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 55 publications
4
8
0
Order By: Relevance
“…Experiments performed in several devices have demonstrated that this assumption is, in general, valid [39][40][41][42], and only in high collisionality plasmas, the contribution of v ph to v ⊥ may become relevant [43,44]. Besides, previous results obtained in W7-X show a good agreement between the experimental E r profiles and those obtained from neoclassical predictions [18,45]. Thus, it is sensible to assume that this condition holds also in the present experiments.…”
Section: Doppler Reflectometry Measurementssupporting
confidence: 77%
See 1 more Smart Citation
“…Experiments performed in several devices have demonstrated that this assumption is, in general, valid [39][40][41][42], and only in high collisionality plasmas, the contribution of v ph to v ⊥ may become relevant [43,44]. Besides, previous results obtained in W7-X show a good agreement between the experimental E r profiles and those obtained from neoclassical predictions [18,45]. Thus, it is sensible to assume that this condition holds also in the present experiments.…”
Section: Doppler Reflectometry Measurementssupporting
confidence: 77%
“…As a consequence, it is difficult to know if the k ⊥ range of fluctuations observed by the DR in these discharges is below or above the spatial scale which should be decorrelated by the shear. As well, other examples exist of instances in which a strong radial gradient of E r seems to be followed by a strong local reduction of the fluctuation amplitude, as measured by the DR. One such case is the strong sheared structure caused in u ⊥ when an island chain of sufficient width is found inside the LCFS [45]. Therefore, while no clear evidence of shear-suppression effect on the turbulence has been found in this work, this analysis will need to be refined before it can be safely stated that there is no such mechanism at W7-X.…”
Section: Discussion and Summarymentioning
confidence: 80%
“…These observations are interpreted in terms of local changes in E r induced by the rational surface that could facilitate or even trigger the L-H transition when the spin-up of the E × B flow takes place at the relevant edge layer. This interpretation is supported by experimental results showing the impact of the magnetic islands on flows and turbulence in TJ-II [67,68] as well as in other devices [69][70][71][72][73] and in numerical simulations [74].…”
Section: (D) Impact Of Magnetic Topologysupporting
confidence: 64%
“…And third, a lower boundary is set to minimize errors in determining the turbulence heatflux Q turb = Q exp − Q NC by avoiding zero crossings of the ambipolar radial electric field E r, and thus ensuring that E r is negative across the entire profile (ion root). E r profile measurements with DR [56] and CXRS [] have confirmed the ion root conditions across the full profile for each power step.…”
Section: Conclusion and Discussionmentioning
confidence: 91%
“…The latter is of utmost important when considering avenues that can suppress ITG turbulence, as is done in e.g. post-pellet experiments [7,8,56]. In W7-X, with its beneficial 3D properties [5,6], a so-called stability valley with elevated a/L T i = a/L n can be achieved when ITGs and densitygradient-driven TEMs, or so-called iTEMs, are simultaneously suppressed [6,7].…”
Section: Modelling Of Ion Turbulent Heat Transportmentioning
confidence: 99%